Comparative Advantages of Intercropping Okra With Selected Vegetables, Okra and Lettuce, Okra and Tomato, Okra and Eggplant, and Okra Sole Crop - Bah, Cherno; Colley, Abbie (International Research & Development for Human Beings (IRDH), 2024)
A field experiment investigating the intercropping of okra with selected vegetables was conducted at the National Agricultural Research Institute (NARI). The study was conducted at the horticultural field of the National Agricultural Research Institute in Yundum. The objective of the study was to assess the effect of okra intercropping with selected vegetables in order to obtain greatest yield and provide better agronomic practices. The field experiment was laid in a RCBD design with four-treatment combination namely: okra intercropped with tomato, okra intercropped with lettuce, okra intercropped with eggplant and the sole of okra. The results showed that there was no significant (P=0.05) interaction between intercropping arrangements and sol okra cropping. Combination of okra with tomato resulted in the higher plant height (23.48 cm) while okra with eggplant resulted in the lowest plant height (18.67 cm). On mean yield, the results indicated that there was no significant (P=0.05) interaction between intercropping arrangements. Okra with tomato supplied resulted in the highest mean yield (571 g per plot) which was not significantly different from sole okra that obtained (343 g per plot). Therefore, to boost okra production, a combination of okra with lettuce will be the best combination package to obtained maximum yield.